Efektivitas Latihan Menggunakan Penghalang Gawang Terhadap Ketepatan Shooting Petanque - Dermawan, Giaz Fathoni; Nurhidayat, Nurhidayat (Universitas Hamzanwadi, 2022)
This research was motivated by the not yet maximal shooting game ability possessed by UMS petanque athletes, considering that there was no preparation of training models to further develop shooting abilities. The purpose of this research is to find out Effects of Implementing Shooting Practice Using Barriers on Shooting Game Ability in UMS Petanque Athletes. The purpose of training using a barrier is to get athletes accustomed to throwing boules to boules. The method used is an experiment using a